Isolamento e caracterização de Bacillus e Lysinibacillus com potencial para controle de pragas agrícolas e insetos vetores - Ferreira, Antonia Débora Camila de Lima (2020)
Pest insects are responsible for causing serious economic and social damage to the population, be it damage to agricultural production or the transmission of diseases to people and animals. Bacillus thuringiensis (Bt) and Lisynibacillus sphaericus (Ls) bacteria are widely studied for pest control due to the insecticidal potential they present to different orders, being exploited mainly for the formulation of bioinsecticides, or as genes donor agents for the construction of transgenic plants. The objective of this research was to prospect new strains of B. thuringiensis and L. sphaericus with insecticidal activity against pests of agricultural importance and vectors diseases. 159 soil samples were processed, giving rise to 125 isolates that were stored in the Invertebrate Bacteria Collection of Embrapa . These isolates were evaluated for their toxicity to insects of Lepidoptera (Spodoptera frugiperda, Helicoverpa armigera and Anticarsia gemmatalis, Coleoptera (Anthonomus grandis) and Diptera (Aedes aegypti and Culex quinquefasciastus) orders. The most pathogenic strains were selected and characterized morphologically by scanning electron microscopy (SEM) and by the protein and molecular profile. After performing the bioassays, was selected at least one strain with high insecticidal activity for each of insects tested. Among the selected strains, S2728 and S2744 showed insecticidal activity for Spodoptera frugiperda and Anthonomus grandis, and presentes crystalline inclusions evidenced by SEM, leading to believe that there were B. thuringiensis. However, the analysis of classical genes for Bt, via polymerase chain reaction (PCR), did not generate any amplification, suggesting that other factors could be associated with the toxicity of these strains, and that is why the genome sequencing of these materials was performed using the Novaseq sequencing system. The analyzes concluded that the strains belong to the complex of B. cereus lato sense group, without revealing exactly the specie. Analysis of ORFs' BLASTn sequences showed the presence of a gene responsible for encoding a protein in the group of Necrosis-Inducing Proteins and ethylene (NEP Like Proteins - NLP). This study also contributed to the enrichment of the EMBRAPA Bacteria Invertebrate Collection, constituting an important genetic resource that can be exploited for other skills besides the insecticidal potential.